Single Moving Average Method Forecasting to Predict Skincare Sales - Marhama, Siti; Sembiring, Muhammad Ardiansyah; Sena, Maulana Dwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Nada Nadine Skincare Store is a business engaged in the sale of beauty skincare. Nada Nadine Skincare Store was established in 2023 and is located on Jalan Lingkungan IV Air Joman, Asahan Regency. The problem at Nada Nadine Skincare Store is that it has difficulty in estimating the level of demand for beauty skincare (Wardah) for inventory because it is still guessing and experience from the production department of Nada Nadine Skincare Store and there is no beauty skincare sales forecasting system that will make it easier for Nada Nadine Skincare Store to determine the amount of beauty skincare (Wardah) inventory. The purpose of this system is to be able to apply the single moving average method to the beauty skincare (Wardah) sales demand forecasting system at the Nada Nadine Skincare Store and to be able to design a website-based beauty skincare (Wardah) sales demand forecasting system at the Nada Nadine Skincare Store using the PHP programming language and MySql database. From the problem analysis, the author tries to predict the amount of beauty skincare demand using the Single Moving Average (SMA) method. The conclusion that can be drawn from research on the Single Moving Average (SMA) based skincare sales forecasting system forecasts the sales demand for beauty skincare (wardah) at the Nada Nadine Skincare Store so The system calculation results are the same as the manual calculation forecast July 2024 is 33,50, forecast August 2024 is 32,75, MAD value is 2,70, MSE value is 11,31 and MAPE value is 8,84%.